PREVENTION AND TREATMENT OF DENGUE BY FEEDING OF CHILDREN UNDER FIVE YEARS: AN INTERVENTION IN HEALTH EDUCATION (Fiep Bulletin - online, 2012)
Dengue is an emerging infectious disease, recognized as important public health problem in the Brazilian population, and its transmission is essentially urban. The literature shows the correlation between the low prevalence of breastfeeding and the emergence of communicable diseases and chronic diseases. In this sense, actions to encourage breastfeeding have been developed to minimize the negative impact of these diseases in the population. This study aimed to present results of a health intervention conducted with parents and responsible of children under 5 years old in a Health Centre located in the city of Macaé, RJ. We conducted an educational intervention on the prevention and treatment of dengue by feeding with parents and responsible of children under 5 years old at the Center for Health Jorge Caldas, located in the city of Macaé, Rio de Janeiro, during the D-Day Campaign for Vaccination polio on August 13, 2011, from 9 am to 17h. During the activity, two academics of the School of Medicine, UFRJ - Macaé, inserted in the Health Surveillance PET/Ministry of Health, between 2010-2011, delivered flyers about the issue and clarify possible questions presented by parents and responsible, and a banner with the following topics: prevention and treatment of dengue by feeding. In the activity, were also collected information on maternal age or responsible and children under 5 years old. We performed a qualitative and quantitative analysis. The educational intervention was conducted with 226 responsible and 271 children under five years. We conclude that the intervention has achieved an important proportion of the population that demanded the center of health, suggesting the positive impact of educational activities at the time of national vaccination campaigns.
Keywords: Health Education; Breastfeeding; Dengue.